Penyuluhan dan Pelatihan Pembuatan Hand sanitizer kepada Dawis Cendrawasih Manyaran Semarang - Noer Abyor Handayani; Aprilina Purbasari; Dessy Ariyanti; Heny Kusumayanti (Sekolah Vokasi Universitas Diponegoro, 2021)
Covid 19 is a disease that can be transmitted through droplet droplets produced when talking, coughing or sneezing. Currently, a clean lifestyle is a demand in socializing, one of which is washing your hands frequently. However, people are constrained to wash their hands frequently when doing activities outside the home. Therefore, people need hand sanitizers as a substitute for soap and water that can be used instantaneously. At the beginning of the pandemic, the number of hand sanitizers on the market dropped sharply because people experienced mass panic, so they made purchases in very large quantities and in a short time. Therefore, training for the community regarding the manufacture of hand sanitizers is necessary. This community service aims to provide training in making handsanitizers to Dawis Cendrawasih mothers in Manyaran Village, West Semarang District, Semarang City. With this training, the community in Dawis Cendrawasih can make their own hand sanitizers so that a healthy lifestyle is maintained.